2013
DOI: 10.1259/bjr.20120428
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal vault brachytherapy in endometrial cancer: verifying target coverage with image-guided applicator placement

Abstract: Objective: This quality assurance study assesses whether CT image-guided verification has led to improvements in the technique when compared with previous studies. Methods:The CT images were studied from a cohort of 105 consecutive patients with endometrial cancer having adjuvant brachytherapy to the vaginal vault in 2010. Images were taken at first insertion, checked for air gaps and treatment delivered. Images were later transferred to the planning system and air gaps between vaginal mucosa and vaginal cylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…In this present study, we found that 75 patients (43%) had $1 air gap with a mean volume of 0.31 cm 3 (range, 0.04-2.93 cm 3 ) and an average distance of mucosa displacement of 3.6 mm (range, 1.8-8.8 mm) with 38.9% of the vaginal mucosa displaced away from the surface of the cylinder by $2 mm. The incidence of air gaps was lower and similar between our study and that of Humphrey et al, 7 because in these studies, the vaginal cylinder with the largest diameter ($3.0 cm) was used more frequently than in other studies (Table 3). Another important finding was that the incidence of vaginal mucosa displaced away from the surface of the cylinder by $2 mm was the highest in patients for whom a smaller diameter cylinder was used compared with other studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this present study, we found that 75 patients (43%) had $1 air gap with a mean volume of 0.31 cm 3 (range, 0.04-2.93 cm 3 ) and an average distance of mucosa displacement of 3.6 mm (range, 1.8-8.8 mm) with 38.9% of the vaginal mucosa displaced away from the surface of the cylinder by $2 mm. The incidence of air gaps was lower and similar between our study and that of Humphrey et al, 7 because in these studies, the vaginal cylinder with the largest diameter ($3.0 cm) was used more frequently than in other studies (Table 3). Another important finding was that the incidence of vaginal mucosa displaced away from the surface of the cylinder by $2 mm was the highest in patients for whom a smaller diameter cylinder was used compared with other studies.…”
Section: Discussionsupporting
confidence: 89%
“…The average total pocket volume was 0.34 cm 3 (range, 0.01-1.32 cm 3 ), and the average distance that the mucosa was displaced was 3.7 mm (range, 1.3-8.0 mm) with 88.8% of the vaginal mucosa displaced away from the cylinder surface by $2 mm. Humphrey et al 7 found that 38 out of 103 patients (37%) had $1 air gap within the target volume, while air gaps $2 mm were seen in only 11 out of 103 patients. In this present study, we found that 75 patients (43%) had $1 air gap with a mean volume of 0.31 cm 3 (range, 0.04-2.93 cm 3 ) and an average distance of mucosa displacement of 3.6 mm (range, 1.8-8.8 mm) with 38.9% of the vaginal mucosa displaced away from the surface of the cylinder by $2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…They show that 3D planning for each fraction does not decrease dose to the normal tissues but incurs greater expense than performing 3D planning for the first fraction only [102104]. CT-based treatment planning effectively allows assessment of air gaps between the applicator and the vaginal cuff prior to treatment delivery [105]. For treatment planning, optimization points should be placed around both the apex and the lateral aspects of the applicator [90].…”
Section: Vaginal Brachytherapy Treatment Deliverymentioning
confidence: 99%
“…They reported that this ratio was lowered to 11 patients by placing larger cylinders in spaces larger than 2 mm and required repositioning, and that there is a significant air gap exceeding 2 mm in only 7% of patients. [51] In two other studies, air gaps exceeding 2 mm were reported with a rate of 32% and 72%. [52,53] However, most of them have little clinical significance, and were reported to include only 0.86% of the vaginal surface.…”
Section: Treatment Preparation and Applicator Selectionmentioning
confidence: 87%